Correspondence between G.A. Hayes-McCoy and Florence O'Donoghue regarding the discovery of papers relating to Irish Volunteer inquiry into the failure of Limerick to participate in the Easter Rising, - Hayes-McCoy, Gerard Anthony, 1911-1975 (1958)
Refers to reports by Donncadh Ó hAnnagáin and George Clancy, statement by M. P. Colivet, and diary of Easter Week events in Tralee, presumed to be by Patrick Cahill.